Analysis of dl-ï¡-tocopherol as antioxidant on malondialdehyde level in pediatric patients with ï¢-thalassemia major - Rismayanti, Levana; Yulistiani, Yulistiani; Andarsini, Mia Ratwita; Qibtiyah, Mariyatul (Folia Medica Indonesiana, 2017)
Thalassemia is a hereditary form of anemia that affects the synthesis of hemoglobin. The management of therapy in patients with b-thalassemia major which patients should receive continuous blood transfusions and increased iron absorption from the digestive tract causes excess iron in the body. This will lead to an increase of free iron level that triggers Radical Oxygen Species (ROS). Increased level of ROS can initiate lipid peroxidation which used as an indicator of oxidative stress in cells and tissues and produce reactive carbonyl, mainly malondialdehyde (MDA). Thus, MDA measurement is widely used as an indicator of lipid peroxidation. On the other hand, the risk of oxidative damage can be reduced by antioxidant, one of them is Vitamin E that is a fat-soluble vitamin with high potential antioxidant. The objective of this study was to analyze the effect of the dl-a-tocopherol (Vitamin E) administration on decrease of MDA serum level on pediatric patients with b-thalassemia major. This was a longitudinal observational study design for one group without comparison was conducted to examine the use of vitamin E to decreased MDA serum level on children patients with b-thalassemia major. The inclusion criteria were patients who rely on blood transfusions, patients who received only one type of iron chelating agents during the study period, the clinical condition is stable, agrees, and has completed the informed consent. In the course of the study of 21 patients there were variations in patient compliance in taking vitamin E tablet dosage 200 IU once-daily for one month: only 11 out of 21 patients consumed 30 tablets of vitamin E 200 IU (total dose of 6000 IU) in the 1-month study, and only data from those 11 samples will be analysed further. MDA serum level was measured pre- and post-administration of vitamin E and patient's characteristics of subjects was obtained for additional information. Pre-administration of vitamin E, serum level of MDA was 1239.4 ± 502.55 ng/mL with a range of 216.95 to 2297.3 ng/mL, whereas in the group post administration of vitamin E, MDA serum level was 786.49 ± 704.88 ng/mL with a range of 6.5380 to 1958.6 ng/mL. In conclusion, there was no significant difference in MDA serum level in the group pre- and post- administration of vitamin E (p = 0.15).